The role of Azerbaijani diaspora organizations in Turkey in shaping the perception of homeland - Şentürk, Sezin.
xii, 226 s. ; 30 cm
Keywords: ► Bu çalışma, Türkiye'deki Azerbaycan diaspora örgütlerinin, kendi üyelerinin anavatan algısının şekillenmesindeki rolünü Azerbaycan diaspora elitlerinin perspektifini göz önünde bulundurarak, tarihsel coğrafya, kültürel ve dilsel bağlar bakımından analiz etmektedir. Türkiye'deki Azerbaycan diaspora örgütlerinin üyelerinin anavatan algısını yeniden inşa eden koşullar, nitel araştırma ile elde edilen bulgular ışığında değerlendirilmiştir. Çalışmada, Türkiye'deki Azerbaycan diaspora örgütlerindeki durumda olduğu gibi, anavatanın tarihsel ve politik sınırlarının her zaman gerçek anavatanla örtüşmediği savunulmuştur. Türkiye'deki Azerbaycan diaspora örgütlerinin Azerbaycan ile duygusal bağları olsa bile, Türkiye Azerbaycan diaspora örgütleri için asıl ve gerçek anavatan durumuna gelmiştir. ► This thesis analyses the role of Azerbaijani diaspora organizations in Turkey in shaping the perception of homeland of members of Azerbaijani diaspora organizations in Turkey from the perspective of Azerbaijani diaspora elites with respect to historical geography, cultural and linguistic bonds. The conditions reconstructing the perception of homeland of members of Azerbaijani diaspora organizations are evaluated in the light of findings obtained through qualitative research. The thesis argues that historical and political boundaries of homeland do not always coincide with the boundaries of real homeland as in the case of Azerbaijani diaspora organizations in Turkey. Turkey becomes the actual and real homeland for the Azerbaijani diaspora organizations although they have emotional connections with Azerbaijan.